Influência da deposição de filmes finos organosilicones na fotodegradação do polipropileno - Mena, Rodrigo Lemes (2013)
It is known that polypropylene is degraded in the presence of UV radiation, making difficult its use in applications where occurs this kind of radiation. This situation arises a need to improve the properties of polypropylene under photodegradation. Some work was done in order to improve the surface properties of the polypropylene film with deposition of organosilicon, but the photoprotection caused by these films is still poorly studied. The purpose of this study was to deposit a film prepared from organosilicon plasmas of HMDSO (Hexamethyldisiloxane) on the surface of polypropylene films and verify the protection provided against photodegradation. Depending on the plasma deposition conditions, we detected a variation in the protection exerted by the deposited film. Among the tests, the chemical vapor deposition on low pressure plasma by radio frequency of 13.56 MHz using a mixture of gases with pressure O2/HMDSO added 6 Pa and a power of 80 W for a period of 1 h showed the best protection results, measured by comparing the evolution of the area in the region with the carbonyl peak at 1722 cm-1. FEG-SEM analysis showed that the film generated have adhesion to the substrate. Profilometry analyzes demonstrated that increasing the deposition time increases the film thickness and decreases its surface roughness.